A FIBONACCI-BASED APPROACH TO ENHANCING VR TRAINING EFFICIENCY: EVIDENCE FROM ENGLISH FOR TECHNICAL FIELDS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This study explores the development of an efficient method for establishing virtual reality (VR) educational laboratories, with a specific focus on English for technical fields. Research indicates that VR-based instructional methods can boost comprehension rates to 75–90% and expedite knowledge acquisition by up to four times compared to traditional teaching. However, extended VR sessions often lead to adverse physical and cognitive effects such as dizziness, eye strain, and fatigue. To address these issues, we propose a Fibonacci-based approach to structuring VR laboratory sessions. By organizing learning intervals according to the Fibonacci sequence and integrating short, periodic breaks, this method enables smoother cognitive transitions, reduces physical discomfort, and optimizes students’ adaptation to and from the virtual environment. A comparative experiment involving 24 students showed that participants who followed the Fibonacci-based method demonstrated statistically significant improvements in learning outcomes and overall well-being when compared to those in continuous VR sessions (p < 0.05).